PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN ALOKASI DANA DESA DI DESA SOSOLAT KECAMATAN MABA UTARA KABUPATEN HALMAHERA TIMUR - Makatangin, Vicktor; Tasik, Femmy C. M.; Kawung, Evelin J. R. (HOLISTIK, Journal Of Social and Culture, 2020)
The Government gave great attention to the development in rural areas. Local governments need to strengthen the implementation of development programmed in rural areas. There is a need for cooperation between local governments and village governments. The cooperation is done through improving the participation of the community, as a form of government and Community cooperation in the building of a region (especially rural areas). In today's autonomous era, aspects of transparency, participation and accountability are very prominent, so decision-making must be strictly based on careful, mature consideration. Governments have the opportunity to solve the problems of poverty in development is always established by the community to have a conscious attitude, real and active role utilizing the potential that has in the effort to increase revenue The whole community.Utilization of National Program the Village Fund Allocation (ADD) in Sosolat Village, North Maba District, East Halmahera Regency is still encountered problem. Village Fund allocation that has not been fully empowered, and has not yet compacted the level of public income with the utilization of village Fund allocation (ADD). Thus, the utilization of Village Fund Allocation (ADD) is expected by the government of East Halmahera Regency can increase community participation in rural development by mutual fund. The development of the village community is aimed to optimally utilize the potential of natural resources and human resource development by improving the quality of life, skills and initiatives with government guidance and assistance..Keywords: Village Fund Allocation, potential, resource